Pengaruh Citra Merek Dan Gaya Hidup Terhadap Keputusan Pembelian Oppo Smartphone (Studi Kasus FEB UNISMA 2017) - Muhammad Muizzuddin Wahid Adly Alwi; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study examines the effect of brand image and lifestyle on OPPO Smartphone purchasing decisions on FEB Unisma 2017 students. The type used is Explanatory Research with a quantitative approach to 90 respondents. This study uses multiple linear regression analysis techniques. The results of the study show that brand image has an effect on OPPO Smartphone Purchase Decisions for Students of the Faculty of Business Economics, Islamic University of Malang in the 2017 batch. Second, Lifestyle has an effect on OPPO Smartphone Purchase Decisions for Students of the Faculty of Business Economics, Islamic University of Malang in the 2017 batch. And thirdly, the influence of brand image and lifestyle together has a simultaneous effect on purchasing decisions. Keywords : Purchase Decisions, Brand Image And Lifestyle.